2008
DOI: 10.1357/002224008788064595
|View full text |Cite
|
Sign up to set email alerts
|

Shelfbreak frontal structure and processes north of Cape Hatteras in winter

Abstract: The circulation north of Cape Hatteras is complicated by the proximity of the shelfbreak front, the Gulf Stream, and convergent shelf flow from the Middle and South Atlantic Bights. A three-week cruise in this region in January/February, 2005 was undertaken in order to study the structure of the shelfbreak front as it terminates near Cape Hatteras and to quantify the freshwater transport from the Middle Atlantic Bight shelf into the Gulf Stream. Two strongly contrasting conditions were identified. Early in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…[, Figure ]) before passing under the Gulf Stream near Cape Hatteras [ Pickart and Watts , ]. Further onshore, along the MAB and Gulf of Maine shelfbreak, a density front between the cooler, fresher shelf waters and the warmer, saltier Slope Sea waters supports the equatorward‐flowing Shelfbreak jet [ Flagg et al ., ; Gawarkiewicz et al ., ]. This is part of the larger shelfbreak current system of coastal circulations between Greenland and the southern MAB [ Fratantoni and Pickart , ].…”
Section: The Northwestern North Atlanticmentioning
confidence: 99%
See 1 more Smart Citation
“…[, Figure ]) before passing under the Gulf Stream near Cape Hatteras [ Pickart and Watts , ]. Further onshore, along the MAB and Gulf of Maine shelfbreak, a density front between the cooler, fresher shelf waters and the warmer, saltier Slope Sea waters supports the equatorward‐flowing Shelfbreak jet [ Flagg et al ., ; Gawarkiewicz et al ., ]. This is part of the larger shelfbreak current system of coastal circulations between Greenland and the southern MAB [ Fratantoni and Pickart , ].…”
Section: The Northwestern North Atlanticmentioning
confidence: 99%
“…Mean along‐shelf flows over the Gulf of Maine and MAB shelf are also equatorward – notably against the mean wind stress, suggesting a mean along‐shelf pressure gradient force [ Lentz , ]. Cold, fresh waters from the equatorward‐flowing MAB shelf and slope currents are entrained into the cyclonic side of the Gulf Stream as “Ford” waters [ Churchill and Gawarkiewicz , ; Gawarkiewicz et al ., ; Csanady and Hamilton , ; Gawarkiewicz and Linder , ; Ford et al ., ].…”
Section: The Northwestern North Atlanticmentioning
confidence: 99%
“…The circulation in the Cape Hatteras region is complicated due to the presence of multiple frontal systems, including the Gulf Sream, the shelfbreak front, and the coastal current flowing southward from Chesapeake Bay (Gawarkiewicz et al, 2008). During the May cruise, we successfully surveyed the shelfbreak front and Gulf Stream.…”
Section: Oceanographic Resultsmentioning
confidence: 99%
“…Evidence that shelf water may commonly be drawn seaward along the northern boundary of water discharged from the Gulf Stream near Cape Hatteras has been presented by Churchill and Cornillon [1991], Gawarkiewicz et al [1996] and Churchill and Berger [1998]. Entrainment of shelf water directly into the Gulf Stream current abutting the shelf‐edge near Cape Hatteras has been observed by Churchill and Berger [1998] and Gawarkiewicz et al [2008]. Churchill and Berger [1998] found that shelf water is often carried to the Gulf Stream along the northern margin of the Hatteras Front, which separates shelf water of the MAB from more saline South Atlantic Bight (SAB) shelf water.…”
Section: Introductionmentioning
confidence: 98%